Pengaruh Gaya Mengajar dan Literasi Digital Terhadap Kreativitas Guru Dalam Pembelajaran Dimediasi Oleh Kompetensi Pedagogik Guru di SMA 1 BONE - Putri Maulidyana Takbir; Mustafa; Syamsu A Kamaruddin (STKIP Subang, 2025)
This study aims to analyze the influence of teaching style and digital literacy on teachers’ creativity in learning, with pedagogical competence serving as a mediating variable. The research focuses on teachers at SMA Negeri 1 Bone, totaling 75 participants, all of whom were included as the sample using a saturated sampling technique. The study employed a systematic literature review approach by gathering relevant articles from databases such as Google Scholar, Scopus, ERIC, and SINTA. The collected literature was examined through thematic analysis and narrative synthesis to identify patterns of relationships among teaching style, digital literacy, pedagogical competence, and teacher creativity. The findings indicate that teaching style has a positive and significant effect on teachers’ creativity, particularly interactive, technological, and personalized teaching styles that encourage educators to develop innovative learning strategies. Digital literacy also contributes significantly to teacher creativity through the ability to utilize technology, evaluate digital media, and design multimedia-based learning content. Furthermore, pedagogical competence plays an essential mediating role by strengthening the influence of teaching style and digital literacy on creativity. Teachers with high pedagogical competence are more capable of integrating varied teaching approaches and utilizing digital tools to create meaningful and creative learning activities. Overall, this study highlights the importance of enhancing teaching style, digital literacy, and pedagogical competence to improve teacher creativity in instructional practices. The findings provide important implications for the development of more comprehensive and sustainable teacher training programs. Keywords: teaching style, digital literacy, teacher creativity, pedagogical competence